Attributions of leaders' charisma increase after their death: The mediating role of identity leadership and identity fusion. (October 2019) - van Dick, Rolf; Fink, Louisa; Steffens, Niklas K; Peters, Kim; Haslam, S. Alexander
In the present research, we replicate previous research showing that death increases attributions of a leader's charisma and that this is mediated by followers' perceptions of a connection between the leader and their group (identity fusion). We also extend previous research by including identity leadership as a further mediator, examining the importance of a leaders' perceived ability to strengthen the identity of the group they lead. Predictions were tested in the unique context of the death of two former German chancellors (Helmut Schmidt, Helmut Kohl) with participants ( n  = 233) evaluating one of these leaders either before or after their death. Results show that the leaders' identity leadership, identity fusion, and charisma were perceived to be significantly higher after their death. Analysis also supported the proposed serial mediation model in which condition (alive or dead) impacted charisma via identity leadership and then fusion. Results support claims that charisma is a social attribution.